Aspectos éticos y legales del asesoramiento genético - Brunet i Vidal, Joan (Psicooncología, 2005)
The genetic data have some features that makes necessary to protect it more than other individual data. There is a wide legal framework related to human genetic data that takes in account this ?excepcionalism?. Along the genetic counseling process, the bioethics principles must be bear in mind and the individual autonomy with an adequate informed consent should be the priority. In some cases, a collision between these principles could appear. The ethical and legal analysis of such situations may help to prevent, identify and resolve them.In the present revision article the reasons for an special protection oh human genetic data will be analyzed, the national and international legal framework will be reviewed, the bioethics principles and its applications to the genetic counseling process will be described, and finally some clinical situations where collisions between principles could appeared will be discussed.